(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
English language proficiency is pivotal in today’s interconnected academic, social, and professional spheres. This study delves into the intricate dynamics of students’ attitudes and initiatives in speaking English in the classroom. The research reveals that students display highly favorable attitudes towards speaking English in academic contexts, associating it with feelings of success, improved personality, and enhanced communicative competence. Moreover, the findings demonstrate students’ high confidence level in English, even when faced with linguistic imperfections, showcasing their willingness to prioritize communication over perfection. The study identifies the significant influence of psychological, linguistic, and learning environment factors on students’ English-speaking abilities, underscoring the need for a comprehensive approach to language learning. Furthermore, the research highlights the positive relationships between students’ confidence, linguistic competence, psychological disposition, personal self-improvement initiatives, and attitudes toward speaking English in the classroom. These insights provide valuable implications for educators and policymakers to create a supportive and engaging learning environment that fosters students’ English language proficiency and encourages a positive attitude towards active participation in English-speaking activities. This study used the descriptive research design to ascertain the attitude, confidence, initiatives, and factors of the English speaking skills of the junior high school students of Union Christian College during the SY 2022-2023. The researchers gathered the data using an adapted questionnaire. Furthermore, they observed ethical guidelines in the conduct of research in the College before gathering data. The data gathered were statistically treated using descriptive and inferential statistics. Problem 1: Students’ Attitude in English Speaking in the Classroom The participants’ responses indicate a highly favorable attitude toward speaking English in academic settings. All items had mean scores above 3 (Moderate Agreement), and most fell into the "Highly Favorable" and "Very Highly Favorable" categories. The results demonstrate that the respondents enjoy speaking English when discussing their thoughts in academic settings, such as classrooms and school forums (Item 1). This enjoyment is further supported by the respondents’ comfort in sharing their thoughts in English during academic gatherings (Item 2). Such positive attitudes towards English language usage in academic settings can contribute to a more engaging and participative learning environment. The data also reveal a sense of confidence among respondents when conversing with teachers in English within the school setting (Item 3). This confidence may lead to more effective teacher-student interactions and foster better communication, positively impacting the learning experience. Respondents strongly associate speaking English in academic settings with feelings of success (Item 4). This suggests that language proficiency may serve as a source of motivation for students, potentially driving them to excel academically. Moreover, the respondents agree on speaking English in general settings (Item 5). This finding reflects the perception that English proficiency is valuable not only in academic contexts but also in various social and professional situations. The participants recognize the multifaceted benefits of speaking English in academic settings. They believe it contributes to their academic success and future job prospects (Item 6). Additionally, English proficiency is perceived as a means to improve one’s personality (Item 7) and communicative competence for interactions outside the academic community (Item 8). Recognizing the personal, academic, social, and economic advantages of speaking English in academic settings (Item 9) further underscores the respondents’ favorable attitudes. This holistic view of the language’s impact demonstrates its significance beyond academic pursuits. Problem 2: Students’ Level of Confidence in Speaking English in Class The results indicate high confidence among students when speaking English in the classroom. Items 1 and 2 demonstrate the highest mean scores, indicating that students are highly confident even when they make errors in pronunciation or lack fluency in grammar. This suggests that students are willing to take risks and prioritize communication over perfection, embracing their imperfections as part of the learning process. Items 3 and 4 show slightly lower mean scores, indicating moderate confidence. However, the standard deviations for these items are relatively high, suggesting a wide range of participant responses. Some students may still experience mild worries about making mistakes or fear being laughed at, which could influence their willingness to participate actively in class discussions. The study’s findings highlight the importance of creating a supportive and inclusive classroom environment that encourages students to take linguistic risks without fear of judgment. Language educators should foster an atmosphere where students feel safe expressing themselves and learning from their mistakes. Problem 3: Students’ Initiatives in Speaking English in Class Among the various self-improvement initiatives, the participants displayed strong motivation in several aspects. They were highly motivated to pay attention to their pronunciation and strive for clarity when speaking (Item 1, M = 4.32). Additionally, they expressed high motivation to engage in activities like reading academic materials aloud (Item 2, M = 3.99) and deliberately expanding their academic vocabulary (Item 3, M = 4.08). The participants valued learning from others and their peers, as shown by their high motivation to observe how people in their field explain complex ideas in English (Item 4, M = 4.11) and to learn from good presenters or classmates who speak convincingly (Item 6, M = 4.13). Participation and interaction in academic settings were also highly regarded, with students seeking opportunities to interact with classmates, professors, and others (Item 5, M = 3.86). Moreover, they demonstrated a strong motivation to prepare key points before class (Item 7, M = 3.59), think about message clarity before speaking (Item 8, M = 4.14), and actively engage in class discussions by listening attentively and contributing to the conversation (Items 10 and 11, M = 3.93 and M = 3.80, respectively). Furthermore, the participants were highly motivated to self-assess and improve their speaking skills. They paid attention to how others agreed and disagreed during discussions (Item 13, M = 3.95), sought opportunities to present (Item 16, M = 3.55), and rehearsed before presentations (Item 17, M = 3.86). After class or presentations, they engaged in reflective practices to identify areas for improvement (Item 19, M = 3.98). The grand mean of 3.92 indicates that the participants were highly motivated across all personal initiatives for self-improvement in speaking English, demonstrating their dedication to enhancing their communication skills in academic contexts. Problem 4: Factors influencing students’ English speaking in class Psychological Factors emerged as the most influential category, with a mean score of 3.61, signifying a high effect on participants’ English-speaking ability. Psychological factors encompass self-confidence, motivation, anxiety, and attitudes toward learning a new language. These findings imply that fostering positive psychological attributes can substantially enhance individuals’ language learning outcomes and overall English proficiency. The mean score of 3.17 for Linguistic Factors indicates a moderate influence on participants’ English-speaking ability. This suggests that language-specific aspects, such as vocabulary, grammar, and pronunciation, significantly determine their proficiency. The moderate effect size suggests that addressing linguistic shortcomings can lead to observable improvements in English speaking skills. The mean score of 3.03 for Learning Environment Factors suggests a moderate impact on participants’ ability to speak English. Learning environment factors encompass the availability of resources, teaching methodologies, and exposure to English in daily life. Although not as influential as psychological factors, addressing learning environment factors can still significantly improve English language proficiency. The overall grand mean of 3.27 indicates a moderate effect size, suggesting that the combined influence of all three factors contributes moderately to individuals’ ability to speak English. This finding reinforces that a multifaceted approach, encompassing linguistic, psychological, and learning environment considerations, is essential for fostering effective language learning outcomes. Problem 5: Relationships between variables Confidence was found to have a significant positive relationship with the respondents’ attitude toward speaking English in the classroom (r = 0.578, p =.001). This result suggests that students with higher confidence levels in their English-speaking abilities tend to have more positive attitudes when using English in the classroom. The implication is that interventions aimed at boosting student’s confidence in their language skills could potentially lead to more favorable attitudes toward English usage during classroom interactions. The Linguistic Factor also demonstrated a significant positive association with the respondents’ attitudes (r = 0.252, p = .003). This finding highlights the importance of linguistic competence in influencing students’ attitudes toward speaking English in the classroom. As students gain proficiency in English language usage, they are more likely to develop positive attitudes toward actively participating in English-speaking activities during classroom sessions. Similarly, the Psychological Factor exhibited a significant positive relationship with attitude (r = 0.205, p = .018). This result indicates that psychological aspects, such as motivation, attitude toward the language, and emotional disposition, play a role in shaping students’ attitudes toward speaking English in the classroom. Educators and policymakers should consider the psychological factors affecting students’ language learning experiences to create a supportive environment that fosters positive attitudes. Furthermore, the Learning Environment Condition was significantly correlated with attitude (r = 0.278, p = 001). This finding emphasizes the significance of the classroom environment in influencing students’ attitudes toward speaking English. Factors like classroom atmosphere, teaching methods, and opportunities for language practice can impact students’ comfort and willingness to engage in English conversations, ultimately affecting their attitudes. Finally, Personal Initiatives for Self-Improvement exhibited a highly significant positive relationship with attitude (r = 0.682, p = 001). This result highlights the importance of students’ proactive efforts in self-improvement, such as engaging in language learning outside the classroom, seeking language partners, or participating in language clubs. Students who take personal initiatives to enhance their English skills are more likely to develop positive attitudes toward using the language in the classroom. This study conducted at Union Christian College, City of San Fernando, La Union, among junior high schools, provides valuable insights into students’ attitudes, confidence, initiatives, and the factors influencing their English-speaking abilities in the classroom. The findings demonstrate an overwhelmingly positive attitude among participants towards speaking English in academic settings, indicating that students enjoy using English to express their thoughts in classrooms and school forums. This positive attitude extends to their interactions with teachers, where students display confidence and perceive English proficiency as a motivation for academic success. The study also reveals that students are highly confident in speaking English, even when facing errors or lacking fluency in grammar, which reflects a willingness to prioritize communication over perfection. However, some students still experience mild concerns about making mistakes or being judged, suggesting the need for a supportive and inclusive classroom environment that encourages linguistic risk-taking. Moreover, the research highlights students’ various self-improvement initiatives to enhance their English-speaking abilities. Participants were motivated to pay attention to pronunciation, expand academic vocabulary, and learn from others and their peers. The findings underscore the importance of fostering a culture of active participation, where students engage in academic discussions, prepare thoroughly, and seek opportunities to present and receive constructive feedback. The study also identifies three significant factors influencing students’ English-speaking abilities: psychological factors, linguistic factors, and learning environment factors. Positive psychological attributes, such as self-confidence and motivation, are crucial in language learning outcomes. Linguistic competence, including vocabulary, grammar, and pronunciation, significantly improves students’ proficiency. Additionally, the classroom environment, teaching methodologies, and exposure to English in daily life.